(untitled) (Journal of the Bangladesh Agricultural University, 2018)
Plants being an important source of medicine play significant role in human health. The aim of the present study was to evaluate thetotal phenolics and carotenoids contents, and free radical scavenging capacity of leaves and fruits of selected five solanaceous medicinal plants, namely Solanum melongena (brinjal), Solanum torvum (tit begun), Solanum virginianum (kantikari), Solanum sisymbrifolium (sada kantikari) and Solanum nigrum (futi begun). Carotenoids content in the leaves and fruits of solanaceous plants varied significantly among the species. Leaf phenolics content ranged between 147.40 (S. melongena) and 585.15 (S. virginianum) mg gallic acid equivalent (GAE)/100 g fresh weight, while fruit phenolics content varied from 50.52 (S. nigrum) to 105.02 (S. virginianum) mg GAE/100 g fresh weight. IC50 values for scavenging 2, 2-diphenyl-1-picrylhydrazyl radical (DPPH) radical ranged between 31.52 (S. nigrum) and 33.55 (S. melongena) mg mL−1 in leaf, while in fruit it ranged between 27.90 (S. virginianum) and 33.11 (S. melongena) mg mL−1. The highest carotenoids content (0.370 mg g−1 fresh weight) was measured from Solanum nigrum leaf. S. virginianum leaf contained about 4−fold high phenolics content than that in S. melongena. S. nigrum leaf had about 15−fold high carotenoids content (0.370 mg g−1 fresh weight). compared to S. torvum and S. virginianum fruits (0.024 mg g−1FW in each). Because of the highest fruit phenolics and carotenoids content along with the lowest IC50 values for scavenging DPPH, S. virginianum fruit can be considered as superior for its health beneficial biochemical constituents J. Bangladesh Agril. Univ. 16(1): 56-61, April 2018